Effect of intravenous fluid supplementation on duration of Phototherapy in term babies with severe hyperbilirubinemia (Indian Journal of Public Health Research & Development, 2025)
Background: Varied results emerging out of various studies have created a controversy about effect of intravenous fluid supplementation on duration of phototherapy required in term babies with severe hyperbilirubinemia. Paucity of literature warrants this study.  Objective: The objective of this study is to evaluate the probable effect, if any, of intravenous fluid supplementation in decreasing the duration of phototherapy requirement in healthy term babies with hyperbilirubinemia. Methods: In this prospective study healthy term neonates      (37-41 week gestation) from day 1 up to 28 days of life with serum bilirubin (>18 mg/dl and
Keywords: Fluid supplementation, Hyperbilirubinemia, Phototherapy